2023
DOI: 10.1038/s41550-022-01850-5
|View full text |Cite
|
Sign up to set email alerts
|

Formation of rocky super-earths from a narrow ring of planetesimals

Abstract: The formation of super-Earths, the most abundant planets in the Galaxy, remains elusive. These planets have masses that typically exceed that of the Earth by a factor of a few; appear to be predominantly rocky, although often surrounded by H/He atmospheres; and frequently occur in multiples. Moreover, planets that encircle the same star tend to have similar masses and radii, whereas those belonging to different systems exhibit remarkable overall diversity. Here, we advance a theoretical picture for rocky plane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…This calls into question the correspondence shown in Figure 1. However, other models argue for "in situ" formation (e.g., Lee et al 2014;Batygin & Morbidelli 2023), and as we discuss below, at earlier stages the nebular gas is warmer with a more distant soot line. Observational tests of these competing ideas are thus strongly desired.…”
Section: Introductionmentioning
confidence: 82%
“…This calls into question the correspondence shown in Figure 1. However, other models argue for "in situ" formation (e.g., Lee et al 2014;Batygin & Morbidelli 2023), and as we discuss below, at earlier stages the nebular gas is warmer with a more distant soot line. Observational tests of these competing ideas are thus strongly desired.…”
Section: Introductionmentioning
confidence: 82%
“…On the other hand, recent simulations show that OGs can also induce a secular resonance sweeping propagating inward through the planet-forming disk, leading to an enhancement of planetesimal rings in the inner regions from which super-Earths can form (Best et al 2023). One pathway that has been proposed to broadly explain the observed architectures of inner multiplanet systems is the so-called "inside-out planet formation (IOPF)" whereby planets form in successive rings of material building up at the magnetorotational instability (MRI) boundary starting at ∼0.1 au (Chatterjee & Tan 2014Hu et al 2016;see Tan et al 2016 for a summary; see also Batygin & Morbidelli 2023 for the formation of multiple small planets from a single narrow ring). As one planet forms and carves a gap in the gaseous disk, the MRI boundary retreats farther out, producing another ring and repeating the process.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…To this end, numerous lines of evidence suggest that the outer solar system itself originated in a compact multiresonant configuration before becoming temporarily unstable and eventually settling in its current state by way of dynamical friction (Batygin & Brown 2010;Nesvorný & Morbidelli 2012). Such a sequence of events may in fact constitute a relatively typical postnebular evolutionary path of planetary systems, and recent modeling has shown that both the period ratio distribution, as well as the degree of intrasystem uniformity of short-period super-Earths, can be satisfactorily reproduced if the majority of systems originate as resonant chains that subsequently relax toward more-widely spaced orbits through dynamical instabilities (Izidoro et al 2017(Izidoro et al , 2021Batygin & Morbidelli 2023).…”
Section: Introductionmentioning
confidence: 99%